Antibacterial activity and structure properties of αFe2O3 nanoparticles synthesized by thermal precipitation method - Habeeb, Saba A.; Hammadi, Asmaa H.; Abed, Dhulfiqar A.; Hamza, Lena F.; Kbah, Noor Z. (Pharmakeftiki, 2025)
In this study, alpha iron oxide (αFe2O3) nanoparticles (NPs) were successfully synthesized via a simple, cost-effective thermal precipitation method, with reaction parameters (such as temperature and alkalinity) systematically controlled in order to ensure high-quality outcomes. The structural and morphological properties of αFe2O3 NPs were characterized using Fourier-transform infrared spectroscopy (FT-IR), scanning electron microscopy (SEM), and X-ray diffraction (XRD). XRD analysis confirmed a hematite phase with an average crystallite size of 24 nm, while SEM imaging revealed NPs of defined morphology with an average particle size of approximately 57 nm. The antibacterial activity of αFe2O3 NPs against the Gram-positive bacterium Staphylococcus aureus was assessed using the agar well diffusion method. The NPs were tested at concentrations of 10, 15, 20, and 25 mg/mL, and their efficacy was compared to that of a standard antibiotic. The results demonstrated notable antibacterial activity at concentrations of 15 mg/mL and above, with clear zones of inhibition observed against S. aureus.